Improved quality of InSb-on-insulator microstructures by flash annealing into melt. (29th January 2021) - Menon, Heera; Södergren, Lasse; Athle, Robin; Johansson, Jonas; Steer, Matthew; Thayne, Iain; Borg, Mattias
Abstract: Monolithic integration of III–V semiconductors with Silicon technology has instigated a wide range of new possibilities in the semiconductor industry, such as combination of digital circuits with optical sensing and high-frequency communication. A promising CMOS compatible integration process is rapid melt growth (RMG) that can yield high quality single crystalline material at low cost. This paper represents the study on ultra-thin InSb-on-insulator microstructures integrated on a Si platform by a RMG-like process. We utilize flash lamp annealing (FLA) to melt and recrystallize the InSb material for an ultra-short duration (milliseconds), to reduce the thermal budget necessary for integration with Si technology. We compare the result from FLA to regular rapid thermal annealing (seconds). Recrystallized InSb was characterized using electron back scatter diffraction which indicate a transition from nanocrystalline structure to a crystal structure with grain sizes exceeding 1 μ m after the process. We further see a 100× improvement in electrical resistivity by FLA annealed sample when compared to the as-deposited InSb with an average Hall mobility of 3100 cm 2 V −1 s −1 making this a promising step towards realizing monolithic mid-infrared detectors and quantum devices based on InSb.